Solomon, the rusty nail - Steig, William, 1907-2003. ([New York] : Farrar, Straus and Giroux, 1987)
Solomon, the rabbit, turns into a rusty nail whenever he scratches his nose and wiggles his toes at exactly the same time and all he does to turn back into a rabbit is think: "I'm no nail, I'm a rabbit." This causes him trouble when a cat wants to eat him.
"A Sunburst book."
School Library Journal
School Library Media Quarterly (A.A.A.L.)
Wilson's Children
4.4
K-3
Keywords: Cats -- Fiction; Magic -- Fiction; Rabbits -- Fiction; Cats -- Fiction; Magic -- Fiction; Rabbits -- Fiction